The effects of cultural value diversity towards multicultural teamwork performance / Zahidah Ab Latif - Ab Latif, Zahidah (2010)
The term multiracial can no longer portray the belief of majoring races include Malay, Chinese, and Indian as quite numbers of ‘additional-colors’ flooding here in Malaysia and the impact had nevertheless to cover certain scopes from industries, services or other ‘inverbal’ benefits. Due to this notion, Malaysian industries depend heavily on foreign workers and in results, Malaysia has imported a large number of foreign workers which resulted in workforce diversity in the service industry like the hospitality industry. This study is undertaken to investigate the relationship between workforce diversity with regard to cultural value diversity that effect multicultural teamwork performance among the local and foreign workers. A total of 150 local and foreign employees from casual ethnic restaurants in Petaling district had participated in this study. Data were collected through self-administered survey questionnaires. Through gathered data, this study shows that the cultural value diversity dimensions namely collectivism, determinism and doing orientation were proved to have positive effect to multicultural teamwork performance (r= .467, p< 0.01). Referring to the empirical analysis results, ‘collectivism value’ has the highest standardized beta coefficient (β = .36, p = .000) and determined as the strongest predictor of multicultural teamwork performance. As to accomplish this study and fulfill the objectives, several positive and negative scrutinizes were excavated. To date, this study exposed the effects of cultural value diversity on multicultural teamwork performance in Malaysia. This study has verified the relationship between cultural value diversity dimensions and multicultural teamwork performance. Therefore, this study provides empirical evidence for the organization in managing the teamwork performance when it contends with cultural differences.